Rattus argentiventer Ricefield - Kazim, Abdul-Rahman; Houssaini, Jamal; Tappe, Dennis; Heo, Chong-Chin (Zenodo, 2022)
Rattus argentiventer (Robinson & Kloss, 1916) Ricefield rat—Tikus sawah Hoplopleura pacifica Ewing, 1924 Polyplax spinulosa (Burmeister, 1838) Published as part of Kazim, Abdul-Rahman, Houssaini, Jamal, Tappe, Dennis & Heo, Chong-Chin, 2022, An annotated checklist of sucking lice (Phthiraptera: Anoplura) from domestic and wild mammals in Malaysia, with lists of hosts and pathogens, pp. 301-336 in Zootaxa 5214 (3) on page 326, DOI:10.11646/zootaxa.5214.3.1, http://zenodo.org/record/7389119